Spatial Autocorrelation Analysis of Agricultural Commodity Regionalization in Buru Regency - Bahasoan, Husen (Cita konsultindo, 2026)
The agropolitan concept is expected to boost farmers' welfare and increase the share of the agricultural sector in the regional gross domestic product (RGDP). The purpose of this study is to examine the distribution pattern of agricultural commodities in Buru Regency based on spatial autocorrelation and to determine agropolitan districts that can be developed based on the results of cluster and outlier analysis. This study uses secondary data and analyzes it using spatial autocorrelation and LQ analysis techniques. The results show that the LQ (Location Quetient) value for rice is relatively uniform in Buru Regency, with only three subdistricts statistically included in the high cluster. The LQ values for tubers are relatively concentrated in Buru Regency, and the High High cluster values for several areas indicate that there are areas with LQ values > 1 in two other subdistricts that function as buffers. Clove LQ values > 1 are found in eight subdistricts in Buru Regency, with only two subdistricts statistically included in the high clove production cluster, while other areas function as buffers. Coconut LQ values > 1 are found in ten subdistricts in Buru Regency, with only five subdistricts statistically included in the high coconut production cluster, while other areas serve as buffers.